Value-Based Monitoring and Evaluation in Islamic Education Governance: Monitoring dan Evaluasi Berbasis Nilai dalam Tata Kelola Pendidikan Islam - Auf, Muhammad Azmi; Widodo, Sembodo Ardi; Pradipa, Rafi; Huda, Syariful; Nazikhah, Ridha Khusnun (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Islamic education has long served as the foundation for shaping character and civilization, but institutional quality often lags behind rapid quantitative growth. Specific Background: Monitoring and evaluation (M&E) are frequently treated as administrative tools, detached from the spiritual values inherent in Islamic education. Knowledge Gap: Few studies have integrated modern management approaches with Islamic ethical principles to build a comprehensive conceptual framework for M&E in Islamic educational settings. Aim: This study explores a value-based M&E model in Madrasah Aliyah Diponegoro Yogyakarta, examining its role in institutional governance. Results: The findings show that M&E functions as a reflective and participatory mechanism that aligns modern quality management with Islamic ethics, strengthens moral identity, and supports sustainable governance. Novelty: This research proposes a synthesized model that bridges technical evaluation methods and spiritual values, positioning M&E as a strategic governance tool rather than a bureaucratic requirement. Implications: The model offers theoretical and practical contributions for policymakers and Islamic educational institutions aiming to establish value-integrated, participatory, and sustainable governance systems. Highlight Value-based monitoring and evaluation integrates modern management and Islamic ethics. Participatory approaches strengthen institutional identity and governance sustainability. The model provides a conceptual and practical reference for Islamic education reform. Keywords Monitoring And Evaluation, Islamic Education Management, Quality Management, Spiritual Values, Madrasah